2002
DOI: 10.1016/s0149-7634(01)00065-3
|View full text |Cite
|
Sign up to set email alerts
|

Orienting of attention in left unilateral neglect

Abstract: After right posterior brain damage, patients may ignore events occurring on their left, a condition known as unilateral neglect. Although de®cits at different levels of impairment may be at work in different patients, the frequency and severity of attentional problems in neglect patients have been repeatedly underlined. Recent advances in the knowledge of the mechanisms of spatial attention in normals may help characterizing these de®cits. The present review focuses on studies exploring several aspect of atten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
141
1
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 286 publications
(151 citation statements)
references
References 152 publications
(190 reference statements)
8
141
1
1
Order By: Relevance
“…As the likelihood of a target appearing at a particular location increases, so does the allocation of attention to that location, and with it, the difference in RTs for targets at valid versus invalid locations. This change in RTs as a function of cue-target validity is known as the proportion validity cueing effect, and historically it was thought to reflect explicit changes in the control of attentional allocation-for example, strategic decisions by a participant to commit attention to a location that is likely to receive a target (Bartolomeo & Chokron, 2002;Castel, Chasteen, Scialfa, & Pratt, 2003;Danckert, Maruff, Crowe, & Currie, 1998: Enns & Brodeur, 1989Jonides, 1981;Kingstone, 1992;Posner, 1980). It has been noted, however, that implicit associations between cue and target locations can also generate a PVE (Bartolomeo et al, 2007;Lambert & Holmes, 2004;Lambert et al, 1999;Lambert & Sumich, 1996;Risko & Stolz, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…As the likelihood of a target appearing at a particular location increases, so does the allocation of attention to that location, and with it, the difference in RTs for targets at valid versus invalid locations. This change in RTs as a function of cue-target validity is known as the proportion validity cueing effect, and historically it was thought to reflect explicit changes in the control of attentional allocation-for example, strategic decisions by a participant to commit attention to a location that is likely to receive a target (Bartolomeo & Chokron, 2002;Castel, Chasteen, Scialfa, & Pratt, 2003;Danckert, Maruff, Crowe, & Currie, 1998: Enns & Brodeur, 1989Jonides, 1981;Kingstone, 1992;Posner, 1980). It has been noted, however, that implicit associations between cue and target locations can also generate a PVE (Bartolomeo et al, 2007;Lambert & Holmes, 2004;Lambert et al, 1999;Lambert & Sumich, 1996;Risko & Stolz, 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…Neuroimaging studies (Corbetta and Shulman, 2002) have demonstrated a right-lateralized, ventral parieto-frontal system important for stimulus-driven, or exogenous attention, which is the form of spatial attention typically impaired in unilateral neglect (Bartolomeo and Chokron, 2002b), whereas a more dorsal parieto-frontal system subserves goal-directed, or endogenous attention. Corbetta and co-workers (2005) recently demonstrated that in left neglect patients the dorsal system can show hemodynamic signs of relative overactivity of the left superior parietal lobule in comparison to its right counterpart.…”
Section: Relation To Models Of Spatial Attentionmentioning
confidence: 99%
“…Relevant neuropsychological evidence from right parietal damage patients found such lesions associated to impairments in contralesional exogenous orienting, with a relative sparing of endogenous orienting (Bartolomeo and Chokron, 2002), thus strongly suggesting the anatomical segregation of those two systems. In contrast, in patients with damage on the temporoparietal junction (TPJ), Friedrich et al (1998) reported extinction-like patterns (related to exogenous orienting) for contralesional targets with larger effects in TPJ than in parietal patients, hence emphasizing the role of parietal regions in the attentional disengagement of endogenous orienting (see also He et al, 2007).…”
Section: Introductionmentioning
confidence: 99%